2019
DOI: 10.1007/s00382-019-04641-3
|View full text |Cite
|
Sign up to set email alerts
|

Classifying past climate change in the Chew Bahir basin, southern Ethiopia, using recurrence quantification analysis

Abstract: The Chew Bahir Drilling Project (CBDP) aims to test possible linkages between climate and evolution in Africa through the analysis of sediment cores that have recorded environmental changes in the Chew Bahir basin. In this statistical project we consider the Chew Bahir palaeolake to be a dynamical system consisting of interactions between its different components, such as the waterbody, the sediment beneath lake, and the organisms living within and around the lake. Recurrence is a common feature of such dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 74 publications
0
48
0
Order By: Relevance
“…Accordingly, several studies demonstrated variable climatic conditions at the Horn of Africa during the Late Pleistocene and Holocene. Transitions from humid to arid conditions and vice versa led to rise and shrinkage of lake levels and also affected the connecting drainage networks (Sagri et al, 2008;Carnicelli et al, 2009;Foerster et al, 2012;Junginger and Trauth, 2013;Foerster et al, 2015;Trauth et al, 2019). We propose that the connected drainage systems in our research area, such as the Bisare River, might have reacted to these transitions with changes in their depositional and erosional behaviour.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Accordingly, several studies demonstrated variable climatic conditions at the Horn of Africa during the Late Pleistocene and Holocene. Transitions from humid to arid conditions and vice versa led to rise and shrinkage of lake levels and also affected the connecting drainage networks (Sagri et al, 2008;Carnicelli et al, 2009;Foerster et al, 2012;Junginger and Trauth, 2013;Foerster et al, 2015;Trauth et al, 2019). We propose that the connected drainage systems in our research area, such as the Bisare River, might have reacted to these transitions with changes in their depositional and erosional behaviour.…”
Section: Discussionmentioning
confidence: 88%
“…The Ethiopian Highlands receive more than 2000 mm of annual rainfall, which is the highest average amount at the Horn of Africa (Griffith, 1972;Viste and Sorteberg, 2013). Annual climatic variations in Ethiopia are related to moisture brought by the summer monsoon that interacts with the dry northeastern "Harmattan" wind system and to changes in the north-south directed pressure gradient (Viste and Sorteberg, E. A. Hensel et al: Prehistoric human settlement activity 205 2013; Nicholson, 2018).…”
Section: Climatic Settingmentioning
confidence: 99%
See 3 more Smart Citations